2019
DOI: 10.1001/jama.2019.12812
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Vaginal Mesh Hysteropexy vs Vaginal Hysterectomy With Uterosacral Ligament Suspension on Treatment Failure in Women With Uterovaginal Prolapse

Abstract: IMPORTANCE Vaginal hysterectomy with suture apical suspension is commonly performed for uterovaginal prolapse. Transvaginal mesh hysteropexy is an alternative option. OBJECTIVE To compare the efficacy and adverse events of vaginal hysterectomy with suture apical suspension and transvaginal mesh hysteropexy. DESIGN, SETTING, PARTICIPANTS At 9 clinical sites in the US Pelvic Floor Disorders Network, 183 postmenopausal women with symptomatic uterovaginal prolapse were enrolled in a randomized superiority clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
50
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 35 publications
11
50
5
1
Order By: Relevance
“…[n=81] vs. 156.7±43.9 min [n=87]) [15,23]. The blood transfusion rate and the difference in Hb levels in our study were comparable with those in a previous study (transfusion, 0.98% [6/610]; difference in Hb, 1.7±1.0 g/dL vs. transfusion, 1.9% [2/108]; difference in Hb, 2.0 g/dL) [24].…”
Section: Discussionsupporting
confidence: 85%
“…[n=81] vs. 156.7±43.9 min [n=87]) [15,23]. The blood transfusion rate and the difference in Hb levels in our study were comparable with those in a previous study (transfusion, 0.98% [6/610]; difference in Hb, 1.7±1.0 g/dL vs. transfusion, 1.9% [2/108]; difference in Hb, 2.0 g/dL) [24].…”
Section: Discussionsupporting
confidence: 85%
“…This is similar to the Scandinavian study where the total mesh group had better apical support [26]. The SUPEr trial [27], a randomized clinical trial of hysteropexy with vaginal mesh augmentation versus a hysterectomy and vaginal vault support, showed that at 36 months the model-estimated failure was 26% for the hysteropexy group and 38% for the hysterectomy group.…”
Section: Discussionsupporting
confidence: 76%
“…Our mean EBL in this study was 179 (± 116) ml. This is slightly higher but still comparable to blood loss reported in the SUPEr trial [27], which randomized 183 women to transvaginal mesh hysteropexy vs. hysterectomy/ ULS (141.1 ± 104.0 ml vs. 147.5 ± 97.4 ml, respectively, p = 0.68). We acknowledge the potential for significant bleeding in this procedure as bilateral paravaginal and pararectal dissection is required; however, with careful technique and attention to hemostasis, hemorrhagic morbidity can be mitigated.…”
Section: Baseline 12 Monthssupporting
confidence: 66%
See 1 more Smart Citation
“…The composite outcome, including prolapse symptoms, prolapse beyond the hymen, or need of reoperation, did not differ between the groups. The authors also reported on the shorter duration of surgery in the vaginal mesh group as well as an 8% erosion rate [19]. Rahkola-Soisalo et al [20] presented a cohort of 164 women treated for POP using the Uphold Lite system.…”
Section: Discussionmentioning
confidence: 98%